Densitometria óssea em crianças e adolescentes fenilcetonúricos - Ana Lucia Pimenta Starling (2005)
Phenylketonuria (PKU), a genetic autosomal recessive disorder, occurs in 1/21.175 newborns in the State of Minas Gerais (Brazil). Its treatment started in early infancy and based on phenylalanine (phe)-restricted diet prevents PKU clinical manifestations, and central nervous system permanent damage. However, due to imposed diet limits, different types and levels of nutritional deficiencies have been found in PKU patients. More frequently, bone mass gain alterations have been reported about PKU patients, but are still not well established. The main objective of this study is to evaluate the presence of alterations in bone mass gain, comparing bone density scans, using the technique of Dual Energy X-ray Absorptiometry DEXA in 49 PKU children and adolescents, and 49 healthy children and adolescents from the control group; matched by sex, age, weight and height. All the 98 individuals of our study took a DEXA scan and the PKU patients also took serum and urinary biochemical dosage tests of Calcium (Ca), Phosphorus (P), Magnesium (Mg) and Alkaline Phosphatasis (PA), and serum biochemical dosage tests of parathormone (PTH) and phe. The daily average intake of Ca, P, Mg and phe was evaluated in this last group, using diet records. Nutritional status, weight gain, height velocity and Z score were evaluated in all individuals of this study. Lumbar spine Bone Mineral Density (BMD) Z scores of both groups were also calculated and compared, using literature-extracted populations of different ethnics, but of the same age and sex. Lumbar spine volumetric BMD was also calculated, using the mathematical formula proposed by KRÖGER (1996). Statistical analysis were performed with EPI-INFO software, version 6.04, distributed by USD, Incorporated, 1999. The results showed significant differences in lumbar spine (BMD), areal and volumetric, with lower averages among PKU patients in comparison with the control group. However, no significant differences were identified between the lumbar spine bone mineral content (BMC) and the whole-body bone mineral density (TBMD), comparing both groups. A significant positive correlation occurred in both groups, comparing age to many different densitometric variables evaluated. The majority of PKU patients showed inadequate Ca, P and Mg intake in all ages studied. Biochemical measures though, showed normal results. No associations were found considering densitometric alterations, minerals intake and biochemical tests. Low patients´ adherence to regimented diet was also observed in PKU patients, due to a high percentage of patients with irregular or inadequate follow-up regimes, considering the annual averages analysis of the serum phe dosages. Only the serum phe levels had a correlation with the PKU patients´ bone densitometric alterations, with lower levels of bone mineralization in those patients with higher levels of serum phe. Lumbar spine (BMD) Z scores differences were found in both groups, only when VAN DER SLUIS et al. (2002) data, obtained from European Caucasian population studies, were used. This study concluded that there is a significant difference of the bone mineral density, only in lumbar spine, with lower average levels found in PKU patients, in comparison with healthy, without PKU, groups, with the same age, sex, weight and height. The serum levels of phe may influence the genesis of the alterations, with lower densities in patients with higher average levels of the amino acid.